(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
The integration of new technologies in teaching English language skills has revolutionized the learning landscape. This paper explores the utilization of digital tools to enhance listening, reading, speaking, and writing abilities. Through the use of podcasts, e-books, video conferencing, and online writing platforms, educators can provide a more interactive and engaging learning experience. The paper highlights the effectiveness of these technologies in catering to diverse learning styles and improving overall language proficiency. It emphasizes the importance of adapting to technological advancements to meet the evolving needs of English language learners